Measurement of Capability Level Using COBIT 5 Framework (Case Study: PT Permodalan Nasional Madani) - Bagas Indra Prasetya; Melissa Indah Fianty; Fahmy Rinanda Saputri (Universitas Islam Raden Rahmat, Malang, 2023)
The development of information technology brings every company to take advantage of the technology they have. The utilization of information technology must be supported by good information technology governance. PT Permodalan Nasional Madani (PNM) is an Indonesian State-Owned Enterprise (BUMN) that is engaged in financial services. PT Permodalan Nasional Madani aims to assist the development of micro, small, medium, and cooperative enterprises. PT Permodalan Nasional Madani uses the PNM Digi application system in running the company. With the existing problems, PT Permodalan Nasional Madani needs to evaluate its IT governance by conducting an information technology audit. In conducting the audit, a framework is needed, namely COBIT 5 to measure the level of capability possessed by the company. This audit is carried out using the information technology audit stages that focus on 4 to 5 COBIT 5 processes that are priority improvements. The results of this audit will be in the form of an audit report containing findings, measurement results of capabilities, impacts if not corrected, level of gaps, and recommendations for improvement to recommendations for increasing levels for PT Permodalan Nasional Madani.